Single factor optimisation of ultrasonic-assisted extraction for recovery of phenolic compounds and its antioxidant activity using one factor analysis / Wan Nor Sofiana Wan Ghazali, Sarmilaah Dewi Subramaniam, Sureena Abdullah and Nurul Aini Mohd Azman - Wan Ghazali, Wan Nor Sofiana; Subramaniam, Sarmilaah Dewi; Abdullah, Sureena; Mohd Azman, Nurul Aini (Universiti Teknologi MARA Shah Alam, 2023)
Bentong ginger (BG) or scientifically known as Zingiber officinale Roscoe, is a popular spice in Malaysia due to its unique pungency taste, spicy aroma, and high nutrition content. BG is classified as traditional medicine and contains abundant bioactive compounds, yet research on BG extraction using ultrasonic-assisted extraction to improve the release of thermosensitive compounds including gingerols is scarce and limited. In this study, the effects of three ultrasonic-assisted extraction (UAE) process factors, namely, amplitude (20–40%), sonication time (10–30 min), and solvent concentration (75–95%), were determined and optimised for maximum yield of phenolics and antioxidants from BG using one factor analysis approach-based Response Surface Methodology (RSM). The optimum extraction conditions for both total phenolic content (TPC) and antioxidant activity (DPPH radical scavenging) were as follows: amplitude of 30.34%, sonication time of 14 min, and solvent concentration of 84%. Regression equations for all experiments revealed that increasing process parameters to a certain level reduced the TPC yield and DPPH inhibition. TPC values vary from 1134.10 to 1313.39 mg GAE/L overall, while DPPH radical scavenging values are between 84.82 and 95.02%.